Analysis of sovereign credit default swap spread during European debt crisis in Spain / Muhammad Hafiz Mohd Shah - Mohd Shah, Muhammad Hafiz (2017)
This thesis represented the determinants of Sovereign Credit Default Swap (CDS) spreads during European Debt Crisis in Spain. The collapse of economy in Spain occurred during the European Debt Crisis started in 2008. The debt crisis led to crisis of confidence for European businesses and economies. Prior to the crisis, CDS spreads were low in Spain, showing the investors have confident and there is a low probabilities of the default of their debts in Spain. After the financial crisis in 2008, the CDS spreads in European countries such as in Portugal, Ireland, Italy, Greece, Spain and Cyprus were raised because the investors relied heavily on foreign capital flows to roll over their debt obligations. Since the crisis, it is clear that investors have become increasingly wary of the distressed Eurozone countries. The CDS spreads continued to rise and reaching newer highs each quarter. This is because the investors fear and have a little faith in the countries' abilities to service their debt obligations. This thesis using statistical approach of ordinary least square to analysed all the variables. The period of analysis is between September 2008 and December 2014. Moreover, volatility index, equity index and bond spread have had a stronger impact on Spain CDS spread since the onset of the recent European Debt Crisis. The main purpose of this thesis will identify sovereign CDS spread in Spain that associated with the current sovereign debt crisis.